Excavations at the Necropolis of the Artyushchenko-2 Site in 2019–2023 - Kashaev, Sergey (Hyperboreus, 2024)
In 2019–2023, systematic investigation of the necropolis and the settlement Artjuschenko-2 continued. During the four last campaigns, an area of about 600 m2 was under examination. In the course of the excavations, 26 graves were discovered (nos. 188–210, Г18–Г20), three of which were examined after modern robbers excavated them. The revealed graves belong to three periods. The earliest ones date to the 5th to 4th centuries BC, the next group to the 3rd to 2nd centuries BC, and the latest to the 4th to 5th centuries AD. It is impossible to precisely date graves that have no inventory or those that have been destroyed by erosion. Various grave constructions have been examined, e. g. crypts built of mudbricks, ground graves with covering, ground vaults, undercut graves, and children’s graves in amphorae. At the settlement, a domestic pit was studied. The ceramic material found in its filling has chronological limits within the second half of the 6th century BC. Thus, the pit contained the earliest finds known for the settlement Artjuschenko-2.